Intrapleural Streptokinase in Parapneumonic / Complicated Pleural Effusion/Empyema: Experience in Dhaka Shishu (Children) Hospital (Bangladesh Journal of Child Health, 2020)
Background: Parapneumonic effusion/complicated pleural effusion/empyema thoracis in children causes significant morbidity. Standard treatment of pleural effusion includes tube drainage and antibiotics. But the tube drainage often fails. Intrapleural Streptokinase has been used in empyema thoracis as well as complicated pleural effusion with good success rate. Though its efficacy is documented in Western literatures and textbooks, there are no clinical trials in children has been reported from Bangladesh.Objectives: We evaluated the efficacy of intra-pleural Streptokinase in the management of Parapneumonic effusion / complicated pleural effusion/ empyema thoracis even in advanced stages.Patients and Methods: A total of 3 patients with parapneumonic effusion requiring intercostal tube drainage, aged 4 year 6 month to twelve years were included in the study who were admitted in Pediatric respiratory medicine unit in Dhaka Shishu (Children) Hospital. Intercostal chest tube drain was given in all patients and inj: Streptokinase (10,000 units/kg/dose) was instilled into the pleural cavity and kept the Streptokinase for 4 hour in pleural cavity. Response was assessed by clinical outcome, after unclamping and serial chest ultrasounds and subsequent chest radiography.Results: Streptokinase enhanced drainage of pleural fluid and complete resolution of effusion in all the 3 patients.Conclusions: Intrapleural Streptokinase is the preferred treatment for treating pediatric empyema/parapneumonic effusion/complicated pleural effusion even in advanced stages and can avoid surgery.Bangladesh J Child Health 2020; VOL 44 (2) :104-108